Bridging Internet of Things and Wireless Sensor Networks: Applications and Challenges - S Shahriar; I Rahaman; A bin Karim; M M Hasan; F Chowdhury; M Sarker (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2020)
With the increasing demand of Wireless Sensor Networks (WSNs) innovations, it cuts numerous zones mobile communication, cloud computing and embedded system in modern living. Inter-net of Things (IoT) is widely used in environmental condition monitoring, logistic support and interfacing sensors and actuators wirelessly, which can be controlled from very long distance. This offers the capacity to control the world from a corner of a room. Wherein sensors and actuators operate reliably with the help of IoT. Wireless data transmission that uses Radio Frequency (RF) has major technical burdens and security vulnerability. The IoT replaced RF as it provides secure transmission capabilities. In this paper, we exhibit a technical overview of WSNs and IoT especially their drawbacks and challenges. Additionally, this paper discusses the progress of the WSNs and IoT innovation.